Local Metric Dimension of Certain Operation of Generalized Petersen Graph - Tadjuddin, Nur Fahri; Nikbakht, Samaneh (Department of Mathematics, Faculty of Sciences and Technology, UIN Syarif Hidayatullah, 2025)
A subset W of V(G) is called a local resolving set of G if r(u│W)≠r(v│W) for every two adjacent vertices u,v∈V(G). The smallest cardinality of all local resolving sets in G is called the local metric dimension of G, denoted by lmd(G). The local resolving set of G with cardinality lmd⁡(G) is called a local basis of G. In this paper, we present a novel study, a topic that has not been extensively explored in previous research, on the local metric dimension of certain operation of generalized Petersen graph sP_(n,1) and determine the lower and upper bounds of